Employing artificial intelligence techniques as a mechanism to activate digital marketing: View global experiences - alit, nassira (Finance and Business Economies Review, 2023)
Given the rapid technological changes that organizations are experiencing today, the employment of digital technologies and the application of artificial intelligence in its activities has become necessary to survive in the market and face competitors and succeed on them, this is reflected in the experiences of most of the world's leading institutions. The research paper aims to try to know the importance of artificial intelligence in digital marketing and to present some of the leading experiences in it to benefit from. The study found that artificial intelligence has a prominent importance through many applications and many examples of brands that have successfully succeeded in outperforming their competitors and gaining the satisfaction of their customers using innovative marketing methods